What model of science? Towards the sociologically - Jedlikowska, Dorota (Journal of Education Culture and Society, 2020)
In the contemporary global world the various models of making and distributing science are cultivated. The particular model of institutionalized science can significantly determine the quality of working both as a scientist and as a student. Research upon science environment in the meaning of investigation the framework of science influences for example the system of communication between different actors engaged in science, good practices, possibilities offered by particular context of science and facilities of acquiring the scientific knowledge etc. It this view the presented paper finds its justification directing analysis towards the quality of making science. Hence the paradigm of sociological science policy is strongly needed. The paper is going to reconstruct the key models which recognize contexts of making science and its numerous dimensions. The research is based on the set of literature founded through the digital key words searching process. The chosen literature recalls the most significant research based on science policy. Consequently the described models tend towards the most globalized and open models of making science to show the path of required changes into still founded coercive science structures mostly institutionalized by long-lasting tradition. The final conclusion states that more concrete steps in reformulating the science policy are required to obtain the desirable model of open science and at the same time to develop the high standing scientific priorities.